PROPERTIES OF THERMOLUMINESCENT CARDS WITH HIGH SENSITIVE GR-200A LiF:Mg, Cu, P DETECTORS FOR HARSHAW AUTOMATIC READER. Issue 4 (12th June 2018) - Tang, K; Cui, H; Qiao, H; Fan, H
Abstract: New DML TL cards with GR-200A detectors were developed. The TL sensitivity remains stable and the detectors were sealed firmly during the encapsulation process. The sensitivity, detection threshold, residual signal, reusability, dose response and Teflon capsule resistance of DML cards with two GR-200A detectors with diameter 3.6 mm and thickness 0.38 mm placed in positions 2 and 3 were evaluated. The detection thresholds were 0.61 μSv for the detector at position 2 and 1.15 μSv for the detector at position 3. The residual signals were 0.40% for the detector at position 2 and 0.57% for the detector at position 3. The 10 repeated readings of the same 10 irradiated cards were found within 1% for the two detectors on the cards. The DML cards demonstrate very high sensitivity, low background and good stability and can be used for very low dose ranges in personnel dosimetry and in environmental monitoring.